Queer in transition - Lugarić Vukas, Danijela; Jelača, Dijana (2012)
In this paper we analyze a short film Queer (Croatia, 2007) as an example of growing visibility of queer narratives in the context of the building of new nation states in the former Yugoslavia. We ask what it means for such queer narratives to disrupt the flow of reproductive heteronormative ideology at a critical moment of political, economic, and historical transition born out of violent conflicts and wars. Can queer offer an effective counterpoint to new ideological formations that constitute the heterosexual subject as the only sanctioned way to perform legitimate (new nation state) citizenship?
ENG